DAYA TERIMA, KADAR PROTEIN DAN ZAT BESI COOKIES SUBTITUSI TEPUNG DAUN KELOR DAN TEPUNG KECAMBAH KEDELAI - Yulia Kurnia Sari; Annis Catur Adi (Universitas Airlangga, 2017)
Moringa leaves and soybean sprouts is local plant in Indonesia. Moringa leaves and soybeans sprouts have high enough of nutrient content but still less to utilization. Moringa leaves are rich in iron and soybeans sprouts as an alternative food material who source of vegetable protein can be substituted to cookies for supplementary food recovery in the rehabilitation phase. The purpose of this study was to analyze the effect of ubstitution of Moringa leaf powder and flour soybean sprouts against acceptance, the levels of protein, and iron cookies. Type of research was true experimental design with completely randomized design at 2 times replicating. Untrained panelists were used 30 mother ofchildren aged 1-3 years. Product acceptance was tested using statistical analysis Kruskal Wallis (α≤0,05). The result of product acceptance test was the most preferred panelist is cookies F1 (150g wheat flour, flour 10g Moringa leaves and soybean sprouts flour 40g) have modus 3 (like) and protein content 9g and iron content 3,21mg per serving size (100g cookies). Statistical analysis showed significant difference to the characteristic colour (p=0,000), odour (p=0,000), texture (p=0,000) and flavor (p=0,000).